Figure 1: RC LowPass Filter
The first thing to do here is to simplify matters by only considering the phasor response
of the above circuit. This circuit can be treated as a simple voltage divider using the
impedances of the passive elements. The values of the voltage phasors are unimportant
here, as only the ratio of the voltages, which will be used to define a transfer function, is
desired.
The impedance of the resistor, Z
R
,
is simply the value of the resistor, R.
R Z
R
·
The impedance of the capacitor, Z
C
, is slightly more complex.
C j
Z
C
ω
1
·
1 − ≡ j where
The output voltage is related to the input voltage using voltage division as follows:
]
]
]
]
+
·
R C
C
in out
Z Z
Z
V V
Substituting the impedances into the voltage divider formula yields the following:
]
]
]
]
]
]
+
·
R
C j
C j
V V
in out
ω
ω
1
1
Simplifying the fraction by multiplying numerator and denominator by jωC =>
]
]
]
]
+
·
RC j
V V
in out
ω 1
1
Defining some transfer function, H(ω), as the ratio of V
out
to V
in
=>
]
]
]
]
+
· ≡
RC j V
V
H
in
out
ω
ω
1
1
) (
Note the transfer function is a ratio of voltages. Since power is proportional to the square
of voltage,
2
V P ∝ , squaring the transfer function allows one to deal with power
proportions. Now, finding the halfpower frequency for this filter is an exercise in
complex algebra. One simply has to realize that by setting the square of the transfer
function to onehalf is the same as stating that, at a certain frequency, ω
c
(note the
frequency dependence of the transfer function), the power out is half the power in.
2
1
) (
2
· ω H
Taking the square root of both sides =>
2
1
) ( · ω H
The main trick here now is to correctly find the absolute value, or modulus, of the
transfer function. One way to do this is to multiply the numerator and denominator by the
complex conjugate of the denominator.
2 2 2 2 2 2
1 1
1
1
1
1
1
) (
C R
RC
j
C R RC j
RC j
RC j
H
ω
ω
ω ω
ω
ω
ω
+
−
+
·
−
−
⋅
+
·
Now the transfer function is in the form z = a + jb. Finding the modulus is now easily
accomplished recognizing
2 2
b a z + ·
Thus,
( )
2 2 2 2
2 2 2
2 2 2
2
2 2 2
2
2 2 2
1
1
1
1
1 1
1
) (
C R
C R
C R
C R
RC
C R
H
ω
ω
ω
ω
ω
ω
ω
+
·
+
+
·
,
`
.

+
+
,
`
.

+
·
Substituting the above into
2
1
) ( · ω H
yields the following:
2
1
1
1
2
1
1
1
2 2 2
2 2 2
·
+
→ ·
+
C R
C R
ω
ω
Clearly, this implies the following:
1
2 1
2 2 2
2 2 2
·
· +
C R
C R
ω
ω
Solving the above for ω
yields the following:
τ
ω
ω
1 1
1
2 2
2
· ·
·
RC
C R
where τ is the time constant of this RC filter, RC · τ .
The derivations for other firstorder linear passive filter circuits (RC and RL filters) are
analogous to the one presented here.
Now. P ∝ V 2 . One simply has to realize that by setting the square of the transfer function to onehalf is the same as stating that. 1 ωRC H (ω ) = + = 2 2 2 2 2 2 1 + ω R C 1 + ω R C 2 2 (1 + ω 1 + ω 2 R 2C 2 2 R C 2 2 2 ) = 1 1 + ω R 2C 2 2 1 Substituting the above into H (ω) = yields the following: 2 1 1 1 1 = → = 2 2 2 2 2 1+ω R C 2 2 1+ω R C 2 . the power out is half the power in. squaring the transfer function allows one to deal with power proportions. or modulus. at a certain frequency. H (ω) 2 = 1 2 Taking the square root of both sides => H (ω) = 1 2 The main trick here now is to correctly find the absolute value. as the ratio of Vout to Vin => H (ω ≡ ) Vout 1 = Vin R 1 + jω C Note the transfer function is a ratio of voltages. Since power is proportional to the square of voltage. 1 Vout =Vin 1 R + jω C Defining some transfer function. finding the halfpower frequency for this filter is an exercise in complex algebra. H (ω) = 1 1 − jωRC 1 ωRC ⋅ = −j 2 2 2 1 + jωRC 1 − jωRC 1 +ω R C 1 + ω2 R 2 C 2 Now the transfer function is in the form z = a + jb. ω c (note the frequency dependence of the transfer function). H(ω). Finding the modulus is now easily accomplished recognizing z = a 2 +b 2 Thus. of the transfer function. One way to do this is to multiply the numerator and denominator by the complex conjugate of the denominator.
The derivations for other firstorder linear passive filter circuits (RC and RL filters) are analogous to the one presented here.Clearly. this implies the following: 1 + ω2 R 2 C 2 = 2 ω2 R 2 C 2 = 1 Solving the above for ω yields the following: ω2 = 1 R C2 2 ω= 1 1 = RC τ where τ is the time constant of this RC filter. . τ = RC .